Mathematical computations for Peristaltic flow of heated non-Newtonian fluid inside a sinusoidal elliptic duct - Saleem, Anber; Akhtar, Salman; Nadeem, Sohail; Alharbi, Fahad M; Ghalambaz, Mehdi; Issakhov, Alibek (Physica scripta, 2020)
This research work interprets the mathematical study of peristaltic flow of non-Newtonian fluid across an elliptical duct. The heat transfer mechanism for this elliptical duct problem is also considered in detail. The mathematical equations for Casson fluid model are developed and then by using appropriate transformations and long wavelength approximation, this mathematical problem is converted into its dimensionless form. After converting the problem in dimensionless form, we have obtained partial differential equations for both velocity and temperature profiles. These partial differential equations are solved subject to given boundary conditions over elliptical cross sections and exact mathematical solutions are obtained. The results are further discussed by plotting graphical results for velocity, pressure gradient, temperature, pressure rise and streamlines.